SISTEM CERDAS PENAMPUNGAN DAN PEMBERIAN PAKAN IKAN PADA PUSAT BUDIDAYA IKAN BERBASIS MIKROKONTROLER - Muharram, Aditiya; Pangestu, Gema Ilham; Akbar, Muhammad Taufik; Septiani, Sri Kurnia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Common fishery such as the one in âPusat Budidaya Perikanan â, the PKMT teamâs partner, located RM. Kahfi I, No. 1, Kelurahan Cipedak, Kecamatan Jagakarsa is still conducted its fish feeding activity manually. The feeding process is crucially counting on the man power that spreads the food known as âpeletâ directly to the pounds without calculating the amount of the food. For that reason, this PKM Tâs work tries to build a fish feeding system which is economical, automated and hygienic. As a realization, a miniature of Microcontroller-Based Smart Fish Feeding System with special modified features of automated peletâs timer and its dosage scale has been created. These features can be set in accordance to the wishes since the microcontroller is used as âthe systemâs brainâ. It controls the solenoid valve and the DC motor of the pelet storage container to work. Thus, the system can not only measure how much pelet is left but also notify it through a buzzer.